(untitled) (Circe de clásicos y modernos, 2025)
The memory of tyrannicide as the origin of democracy constituted a central element of the ideology that supported the Athenian political system during the classical period. In this sense, the democratic city enabled sites where this memory was linked to specific spaces –particularly the agora– and to certain practices that, in turn, connected various bodies, both living and dead, real and represented, present and absent, contemporary and from the past. This article evaluates those bodies, those spaces, and the connections that developed between them in the imaginary of democracy.